The production of the English stop voicing contrast by Arab L2 speakers of English - Hamzah, Mohd Hilmi; Madbouly, Ahmed Elsayed Samir; Halim, Hasliza Abdul; Abdullah, Abdul Halim (Indonesian Journal of Applied Linguistics, 2020)
The English voiceless stop /p/ and voiced stop /É¡/ are absent in the consonant inventory of Arabic. This difference provides a fertile ground for empirical research in L2 speech learning among Arab L2 speakers of English. The current study, therefore, aims to explore the English stop voicing contrast as produced by Arab native speakers. Focusing on Voice Onset Time (VOT) as an acoustic parameter, the study seeks to examine the extent to which (1) Arab L2 speakers of English maintain the English stop voicing contrast for /p-b/ and /k-É¡/, and (2) the L2 VOT continuum by Arab L2 speakers follows or deviates from the L1 VOT continuum in English. The acoustic phonetic experiment involved elicited materials of /p-b/ and /k-É¡/ from four male native speakers of Arabic. The tokens were recorded in isolation (utterance-initial position) and in a carrier sentence (utterance-medial position). The data were then acoustically analysed following standard segmentation, annotation and measurement criteria. Results reveal that the Arab L2 speakers can, to a large extent, maintain the English stop voicing contrast across all places of articulation, with voiced stops usually being produced with â€œnormalâ€ negative VOT (prevoicing) and voiceless stops usually being produced with â€œnormalâ€ positive VOT and also accompanied with aspiration in the long-lag region. There are also exceptional cases of â€œabnormalâ€ negative VOT (prevoicing) for voiceless stops and â€œabnormalâ€ positive VOT (devoicing) for voiced stops, with an extremely larger number of devoiced tokens for voiced stops in comparison to prevoiced tokens for voiceless stops. The results accord well with the Speech Learning Modelâ€™s prediction that phonetically â€œnewâ€ sounds are relatively easier to learn than phonetically â€œsimilarâ€ sounds. The conclusion is drawn that languages sharing the same sound contrast may exhibit different phonetic implementations in marking a phonological contrast.